First aid manual - Piazza, Gina M.; American College of Emergency Physicians (London ; New York : DK, 2009)
Showing you how to treat someone suffering from over 100 medical conditions and injuries, whether a minor burn or a heart attack, this latest edition of the best-selling "American College of Emergency Physicians First Aid Manual" gives you the knowledge you need instantly if someone becomes ill or gets hurt.
Introduction -- Becoming a first aider -- Managing an incident -- Assessing a victim -- The unconscious victim -- Respiratory problems -- Wounds and circulation -- Bone, joint, and muscle injuries -- Nervous system problems -- Effects of heat and cold -- Foreign objects, poisoning, bites, & stings -- Medical problems -- Techniques and equipment -- Emergency first aid -- First aid regulations -- Index -- Acknowledgements.
Includes index.
Keywords: First aid in illness and injury -- Handbooks, manuals, etc